PROBLEMA ORANG TUA DALAM MELANJUTKAN PENDIDIKAN ANAK KE SEKOLAH LANJUTAN TINGKAT ATAS DI KELURAHAN GERUNG SELATAN KECAMATAN GERUNG KABUPATEN LOMBOK BARAT TAHUN 2019/2020 - Wirrahman, Wirrahman; Sugiyono, Sugiyono; Rusfandi, Rusfandi (Jurnal Penelitian dan Pendidikan IPS, 2025)
This study aims to analyze the factors that cause parents not to continue their children's education to SLTA and the efforts made to overcome these problems. This research employs a qualitative approach using observation and interviews with parents, students, and school representatives. The findings indicate two main factors influencing parental decisions: internal and external factors. Internal factors include children's lack of interest in learning and the dominance of psychomotor skills, which make them more inclined to work rather than continue schooling. External factors include economic difficulties, low parental education levels, weak parental control over children's education, and social environment influences that prioritize economic success through direct employment. Despite these challenges, the community in Gerung Selatan Village has made efforts to support children's education, such as preparing educational facilities by improving family economic conditions and conducting awareness campaigns about the urgency of education in collaboration with the government, schools, and universities in West Lombok and Mataram